Distinguishing Facts and Opinions: Enhancing Students’ Critical Reading Skills Using Pair Checks Method - Sari, Mita Nurindah; Ramli; Sari, Puspa (FKIP, Universitas Lakidende Unaaha, 2024)
This study investigates the effectiveness of the Pair Checks method in improving eleventh-grade students’ ability to distinguish between facts and opinions in discourse texts. Conducted through two cycles of Classroom Action Research (CAR), the study shows significant improvements in student performance, engagement, and collaboration. In Cycle I, students demonstrated moderate improvement in their ability to identify facts and opinions, with an average score increase from 63 to 74.44. However, challenges such as limited student engagement were addressed in Cycle II, leading to further enhancements, with the average score rising to 81.33 and 83.33% of students achieving the minimum competency level. Observational data revealed improved classroom behavior, increased participation, and reduced disruptions, demonstrating the positive impact of the method. The findings support the application of cooperative learning strategies in fostering critical thinking, analytical skills, and media literacy. This study highlights the value of iterative refinements in instructional methods and suggests that the Pair Checks method can be an effective tool for enhancing students’ reading comprehension and critical engagement with texts. Future research could explore broader sample sizes and longitudinal studies to assess the long-term impact of this approach.